2010
DOI: 10.1038/aja.2010.93
|View full text |Cite
|
Sign up to set email alerts
|

Rat recombinant β-defensin 22 is a heparin-binding protein with antimicrobial activity

Abstract: Approximately 40-50 b-defensins are predominantly expressed in the male reproductive system of mammals. This selective expression raises the question as to the roles of these molecules in innate immunity and fertility in the male reproductive tract. Rat b-defensin 22 is an epididymis-specific b-defensin expressed in segments 12-14 of the epididymis. This protein contains both b-defensin and lectin signature sequences, yet its antimicrobial activity and carbohydrate-binding ability have not been shown. We herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
(68 reference statements)
1
18
0
1
Order By: Relevance
“…However, βD22 LD had no antimicrobial activity against Gc (Figure 7). These results indicate that the defensin domain of βD22 is necessary and sufficient for antigonococcal activity, in agreement with previous findings in E. coli and C. albicans (Diao et al, 2011;Liu et al, 2013).…”
Section: The Defensin-like Domain Is Responsible For the Antigonococcsupporting
confidence: 82%
See 4 more Smart Citations
“…However, βD22 LD had no antimicrobial activity against Gc (Figure 7). These results indicate that the defensin domain of βD22 is necessary and sufficient for antigonococcal activity, in agreement with previous findings in E. coli and C. albicans (Diao et al, 2011;Liu et al, 2013).…”
Section: The Defensin-like Domain Is Responsible For the Antigonococcsupporting
confidence: 82%
“…Beyond this, β-defensins within species have highly dissimilar protein sequences (Rao, 2002;Patil et al, 2005). Notably, we found that the antimicrobial activity of βD22 is localized to its defensin domain, as reported for other gram-negative bacteria and fungi (Diao et al, 2011;Liu et al, 2013). The percent identity between βD22 and a canonical β-defensin, βD2, is low (20%).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations